Pengaruh CAR, LDR, dan Inflasi terhadap ROA pada Bank Umum yang Terdaftar di BEI - Aminah Fitrieska Pratami (Indonesian Journal of Economics and Management, 2021)
The aim of this research are to know the effect of CAR, LDR, and Inflation to ROA at a Commercial Bank Listed on IDX Period 2014-2018. The population on this research are commercial bank that already listed on IDX Period 2014-2018. The samples used were 31 bank companies is using random sampling or taking samples randomly using the Slovin formula. The analytical used is to know the effect of CAR, LDR, and Inflation to ROA is multiple linear regression analysis using IBM SPSS 25 Software. This research showed that CAR, LDR, and Inflation are simultaneously react significantly to ROA. CAR and LDR has a positive and significant effect on ROA, therefore Inflation are not having significant effect partially to ROA.